2022
DOI: 10.1158/1078-0432.ccr-22-0980
|View full text |Cite
|
Sign up to set email alerts
|

An Ex Vivo Organotypic Culture Platform for Functional Interrogation of Human Appendiceal Cancer Reveals a Prominent and Heterogenous Immunological Landscape

Abstract: Purpose: Epithelial neoplasms of the appendix are difficult to study preclinically given their low incidence, frequent mucinous histology, and absence of a comparable organ in mice for disease modeling. While surgery is an effective treatment for localized disease, metastatic disease has a poor prognosis as existing therapeutics borrowed from colorectal cancer have limited efficacy. Recent studies reveal that appendiceal cancer has a genomic landscape distinct from colorectal cancer and thus preclinical models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…While these cells lacked features suggestive of anti-tumor activity, their cytotoxic potential could be harnessed further for strategies that aim to convert bystander cells into infiltrating cells that can contribute to anti-cancer activity (52). This is further supported by recent studies that demonstrated an ex vivo T cell activation in PMP tumors (55)(56)(57).…”
Section: Pmp Could Indicate Either Anti-tumor Cells or Bystander Cell...mentioning
confidence: 89%
See 1 more Smart Citation
“…While these cells lacked features suggestive of anti-tumor activity, their cytotoxic potential could be harnessed further for strategies that aim to convert bystander cells into infiltrating cells that can contribute to anti-cancer activity (52). This is further supported by recent studies that demonstrated an ex vivo T cell activation in PMP tumors (55)(56)(57).…”
Section: Pmp Could Indicate Either Anti-tumor Cells or Bystander Cell...mentioning
confidence: 89%
“…Importantly, these cells retained cytotoxic gene expression suggesting they could be targeted for therapeutic purposes. Recent studies have demonstrated that PMP tumors can respond ex vivo to immune checkpoint blockade or neoantigen vaccination (55)(56)(57). Further functional characterization of this lymphocyte infiltrate will help clarify the role of these cells in anti-cancer immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Ubc9-deficient Tregs in mice lost Foxp3 expression upon T cell receptor (TCR) stimulation [ 6 ]. In primary patient tumor tissues, pharmacological SUMOylation inhibition reduced Tregs [ 7 ] ( Figure 2 ).…”
Section: Sumoylation Inhibition Suppresses Tregs and Enhances Effecto...mentioning
confidence: 99%
“…As such, the reliance of Treg expansion and function on SUMO serves as an appealing target. Ding et al reported that the knockout of UBC9 (the SUMO E2 ligase) in a Treg population resulted in impaired proliferation, activation, and suppressive functionality ( Weitz et al, 2022 ). Similarly, Lam et al (2023) treated T-cell populations from patients with chronic lymphocytic leukemia with TAK-981 and reported decreased Treg differentiation.…”
Section: Opportunities For Sumo-augmented Oncolytic Viral Immunothera...mentioning
confidence: 99%
“…As such, the implication of SUMO in the pathogenesis of resistant cancers has positioned SUMOtherapeutics as potential anti-cancer agents and immunotherapeutic adjuvants ( Seeler and Dejean, 2017 ). The first SUMOtherapeutic, TAK-981 (Takeda Pharmaceuticals, Tokyo, Japan), has been reported to induce cell-cycle arrest ( Hanel et al, 2022 ; Kim et al, 2023 ), deplete Treg populations ( Weitz et al, 2022 ) and spur immune activation ( Khattar et al, 2019 ; Lightcap et al, 2021 ; Kumar et al, 2022 ), giving rise to increasing efforts to apply it to a wide set of cancers ( Langston et al, 2021 ) ( Figure 1 ). TAK-981 is presently being investigated for advanced non-small cell lung cancer, cervical cancer, microsatellite-stable colorectal cancer, refractory or relapsed diffuse large B-cell lymphoma, and follicular lymphoma (NCT03648372).…”
Section: Introductionmentioning
confidence: 99%